The Use of Mā forms in Surah Yāsīn and its various translations - Ahmad Hifni; Muhammad Syahid Ridha; Herawati Irawan; Muhammad Fathul Barri (LITTERATURA: Jurnal Bahasa dan Sastra, 2022)
This research seeks to identify and introduce the function and meaning of mā and to describe techniques for translating it into Indonesian especially in the Qur'an. The method used is a qualitative method based on library research. The data sources used are the types of mā forms found in Surah Yāsīn and in the translation will be shown a comparison of the translations of the Lajnah Pentashihan Mushaf Al-Qur'an in 2019 and Lembaga Percetakan Al-Qur’an Raja Fahd in 1997. The results of this study state that There are five forms of the eight forms of mā in the Surah Yāsīn, totaling 32 data from 26 verses. The five forms are al-istifhāmiyyah with 1 data, namely in verse 22, al-mauṣūliyyah with 16 data, namely in verses 12, 35, 36, 42, 45, 47, 52, 54, 57, 64, 65, 71, and 76, al-masdariyyah has 1 data in verse 27, al-nāfiyyah has 12 data in verses 6, 15, 17, 28, 30, 46, 49, 67, and 69, and al-zaidah has 2 data in verses 11 and 82. As for the form of translation, al-istifhāmiyyah is often translated with interrogative sentences, al-mauṣūliyyah is translated as 'which', al-masdariyyah can be translated in noun form, al-nāfiyyah is mostly translated 'no', and mā al-zāidah is often not translated into Indonesian.